Monitoring of antimicrobial resistance in hospital, municipal, and treated wastewater in Mbarara, Uganda - Claudia Stange; Rogers Kalyetsi; Judith Owokuhaisa; Moses Ntaro; Arthur Leon; Paul R. Hunter; Andreas Tiehm; Edgar M. Mulogo (Journal of Global Antimicrobial Resistance, 2025)
Objective: The aim of this study was to estimate the prevalence of antimicrobial resistance in the population of Mbarara through analysis of wastewater and determine the effectiveness of wastewater treatment in reducing discharge of antibiotic-resistant bacteria and antibiotic resistance genes into the environment. Methods: Hospital, municipal, and treated wastewater (collected on 10 different dates) from Mbarara, Uganda, were analysed for extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli using a culture-based method and selected clinically relevant antibiotic resistance genes using quantitative PCR. Results: The finding of this study demonstrated that 30.6% of the total E. coli were ESBL producers, constituting a high proportion compared to studies in other countries. Furthermore, the investigation revealed the widespread distribution of the carbapenemase gene blaCMY-2 within the population. The comparative study of the inflow and outflow of the waste stabilisation pond system, which is used for wastewater treatment, demonstrated a log reduction of 1.9–2.4 for coliform bacteria and total as well as ESBL- producing E. coli . Conversely, the wastewater treatment was associated with an increase of the antibiotic resistance genes sul1 and tetC. Conclusions: The study shows that the waste stabilisation pond system is releasing significant amounts of coliform bacteria, E. coli , ESBL-producing E. coli , somatic bacteriophages, and antibiotic resistance genes into the Rwizi River. We also demonstrated that wastewater-based surveillance is a cost-effective method of obtaining information on the prevalence of AMR in the population, especially in countries where clinical surveillance is limited due to a lack of resources and infrastructure.
Keywords: Antimicrobial resistance; Antibiotic resistance genes; Wastewater; Wastewater treatment da; Extended-beta-lactamase-producing E. coli; Uganda